Razmerje med ksilemskim in floemskim prirastkom pri jelki (Abies alba Mill.) - Krže, Luka (Zbornik gozdarstva in lesarstva, 2007)
In 10 silver firs (Abies alba), the following was investigated: anatomical structure of phloem growth rings (FB) in relation to their width, ratio between number of cell-layers in FB and in xylem growth rings (KB), variation in number of cell layers in FB and KB around the stem circumference, relation between widths of FB and KB formed in the same year, and the width of dormant cambial zone (KC). Samples of intact tissues were taken from living trees in 2001 and 2002, and permanent cross-sections for light microscopy prepared. We observed the relationship between width and anatomical structure of the FB. Narrower FB contained more early phloem, whereas wider FB contained more late phloem cells. Wider FB sometimes contained an additional band of axial parenchyma. The KB were 2 to 21 times wider than the FB. The widths of KB varied around the stem circumference more than the widths of FB. The widths ofdormant KC were positively correlated to the widths of FB and KB.
Keywords: Abies alba Mill.; floem; kambij; ksilem; les; navadna jelka; prirastek